Activity Test of Durian Peels Essential Oil (Durio zibethinus) as an Antipediculosis Against Pediculus humanus capitis Linn. (Anoplura: Pediculidae) - Yuli Wahyu Tri Mulyani; Siti Nurjanah; Samsuar Samsuar; Laila Susanti (Universitas Sebelas Maret, 2021)
Pediculosis is a disease caused by infestation of head lice (Pediculus humanus capitis) which is a blood-sucking obligate ectoparasite. The essential oil of durian fruit peel has active compounds that have the potential as vegetable pediculosides that can kill head lice. This study aimed to find the best concentration of essential oil from durian fruit peels that can kill head lice. The research design used with an essential oil concentration of 100%, 75%, 50%, 25%, distilled water as negative control and permethrin 1% as positive control, three repetitions and each concentration consisting of 10 flea tails. The parameters observed were the condition of lice morphologically based on the activity of limb movement, antenna movement and digestion, then the calculation of mortality was observed based on the time of the test. The results showed that the concentration of durian peel essential oil as an antipediculosis had a significant effect on the time of death of head lice, limb movement and digestion. The test result showed that the concentration is 100%, has a death time of 12 minutes 32 seconds, 75% concentration was 16 minutes 28 seconds, 50% concentration was 21 minutes 11 seconds, 25% concentration was 32 minutes 23 seconds, negative control was 61 minutes 15 seconds. The fastest time of death in positive control for chemical pediculosides was 10 minutes 15 seconds. The conclusion in this study was that essential oils the dominan one is 1,5-naphthyridin-2-amine were proven to kill head lice and the best concentration was close to positive control, namely at a concentration of 100%.